ANALISIS PENGARUH KOMPETENSI, KOMITMEN DAN MOTIVASI TERHADAP KINERJA DOSEN JURUSAN MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PATTIMURA AMBON - Saleh Tutupoho (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
The condition of lecturers at the Faculty of Economics and Business can be seen that there are still many lecturers who have not carried out of tridharma activities, only limited to education and teaching activities. There are still many lecturers who carry out Tridarma research and dedication only to take care of the academic level. Not yet used as a target of the performance of the lecturers themselves. Competence, commitment and motivation are the main factors that influence the performance of private university lecturers. This study aims to obtain the results of studies on competency, commitment, motivation and performance of lecturers and to reveal the analysis of the influence of competence, commitment and motivation on the performance of lecturers.The research method used is descriptive and explanatory survey with a questionnaire as a primary data collection tool. The sample size of 45 lecturers was taken through a purposive random sampling technique, with lecturer information sources spread across the Management Department of the Faculty of Economics and Business. Data analysis using multiple regression tests with SPSSThe results of this study are that there is a significant effect of competence on the performance of lecturers, then there is a significant influence on commitment to lecturer performance and there is a significant effect of motivation in improving lecturer performance and significant influence jointly on competence, commitment and motivation on lecturer performance.